PD-1 Blockade Modulates Functional Activities of Exhausted-Like T Cell in Patients With Cutaneous Leishmaniasis - Garcia de Moura, Renan; Covre, Luciana Polaco; Fantecelle, Carlos Henrique; Gajardo, Vitor Alejandro Torres; Cunha, Carla Baroni; Stringari, Lorenzzo Lyrio; Belew, Ashton Trey; Daniel, Camila Batista; Zeidler, Sandra Ventorin Von; Tadokoro, Carlos Eduardo; de Matos Guedes, Herbert Leonel; Zanotti, Raphael Lubiana; et al. (Frontiers in Immunology, 2021)
Patients infected by Leishmania braziliensis develop debilitating skin lesions. The role of inhibitory checkpoint receptors (ICRs) that induce T cell exhaustion during this disease is not known. Transcriptional profiling identified increased expression of ICRs including PD-1, PDL-1, PDL-2, TIM-3 and CTLA-4 in skin lesions of patients that was confirmed by immunohistology where there was increased expression of PD-1, TIM-3 and CTLA-4 in both CD4+ and CD8+ T cell subsets. Moreover, PDL-1/ PDL-2 ligands were increased on skin macrophages compared to healthy controls. The proportions PD1+, but not TIM-3 or CTLA-4 expressing T cells in the circulation were positively correlated with those in the lesions of the same patients, suggesting that PD-1 may regulate T cell function equally in both compartments. Blocking PD-1 signalling in circulating T cells enhanced their proliferative capacity and IFN-γ production, but not TNF- secretion in response to L. braziliensis recall antigen challenge in vitro. While we previously showed a significant correlation between the accumulation of senescent CD8+CD45RA+CD27- T cells in the circulation and skin lesion size in the patients, there was no such correlation between the extent of PD-1 expression by circulating on T cells and the magnitude of skin lesions suggesting that exhausted-like T cells may not contribute to the cutaneous immunopathology. Nevertheless, we identified exhausted-like T cells in both skin lesions and in the blood. Targeting this population by PD-1 blockade may improve T cell function and thus accelerate parasite clearance that would reduce the cutaneous pathology in cutaneous leishmaniasis.